Competências requeridas dos gerentes de projetos de transformação digital para o tratamento dos impactos nas organizações - Oliveira, Henrique Pontes Gonçalves de (2021)
Digital Transformation projects have been growing at an accelerated pace in organizations, transforming their ways of doing business and substantially impacting organizational elements— such as business and operational processes, organizational culture, employees, customers, and partners. Due to this acceleration and scope, Digital Transformation projects have different particularities. They require that Project Managers develop new or improved skills and behavioral competences to act not only in project management but also in dealing with the impacts generated. Therefore, Project Managers’ behavior and responsibilities must be reviewed and changed to fulfill this role. This work researched which competences are necessary for Project Managers to work in Digital Transformation projects through multiple case studies. After the theoretical framework on digital technologies, Digital Transformation projects, project management, organizational elements, impacts, treatment and competences of the Project Managers, four propositions were elaborated to answer the research question. The first proposition is that Digital Transformation projects have different particularities compared to traditional IT projects; the second questions whether Digital Transformation projects impact organizations; the third, whether the impacts generated by Digital Transformation projects can be treated with appropriate actions by Project Managers; and the fourth, whether Digital Transformation projects require Project Manager to improve or develop new skills. In the study, all propositions were confirmed. The data collection stage was carried out in five large companies and, in each of them, a Digital Transformation project was studied. In the five projects studied, we found that the projects strongly affected organizations, positively and negatively, and each treatment should be applied with different actions by project managers. The main results point to the development and improvement of behavioral skills and technical skills should be simplified. Project Managers’ profile should be “hybrid”, with knowledge on IT and business areas, but greater emphasis on the business area.